THE IMPORTANCE OF TEACHING VOCABULARY TO B1 LEVEL STUDENTS (SYNAPSES: INSIGHTS ACROSS THE DISCIPLINES, 2025)
Vocabulary acquisition is an important aspect of language learning, especially for B1-level students who are shifting from basic to advanced language skills. This article looks at the significance of vocabulary instruction for B1 students, the contrast between different types of vocabulary (verbal vs. print, receptive vs. productive), and effective teaching methods. The research emphasizes the importance of vocabulary in reading comprehension, communication abilities, and general language ability. It also provides research-based vocabulary teaching tactics, such as contextual learning, scaffolding, and active engagement techniques.